2003
DOI: 10.4141/a02-002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neural network and multiple regression predictions for 305-day lactation yield using partial lactation records

Abstract: A comparison of neural network and multiple regression predictions for 305-day lactation yield using partial lactation records. Can. J. Anim. Sci. 83: 307-310. Milk yield predictions based on artificial neural etworks and multiple regression were studied. The 305-d lactation yield predictions were based on milk yield of the first 4 test days. Average 305-d milk production of the herd, number of days in milk and month of calving. The predictions made with either the neural network or the multiple regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 7 publications
0
42
0
1
Order By: Relevance
“…However, 305-d milk yield prediction by MLR was lower than the observed 305-d milk yield by 629.4 kg (P <0.01). Grzesiak et al (2003) used ANN and MLR in their study, showing there was no significant difference between observed values and predicted values (P >0.05) suggesting that ANN was appropriate for modelling 305-d milk yield. The average 305-d milk yield predicted by the ANN was lower than the average observed yield of the 49 reference cows by 13.12 kg ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 305-d milk yield prediction by MLR was lower than the observed 305-d milk yield by 629.4 kg (P <0.01). Grzesiak et al (2003) used ANN and MLR in their study, showing there was no significant difference between observed values and predicted values (P >0.05) suggesting that ANN was appropriate for modelling 305-d milk yield. The average 305-d milk yield predicted by the ANN was lower than the average observed yield of the 49 reference cows by 13.12 kg ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…y was the actual value, n was the total number of records (Salehi et al, 1998;Grzesiak et al, 2003). Ratio of mean (RoM) described by Friedrich et al (2008) was calculated as:…”
Section: Figure 1 Architecture Of Artificial Neural Network (Ann) Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Grzesiak et al (2003) Data were analyzed using a neural network, the so-called Self-organizing Map, SOM (Kohonen, 1997). This network was formed by elementary units, neurons, in a bidimensional network.…”
Section: Artificial Neural Network: Self Organizing Mapsmentioning
confidence: 99%
“…A similar study on the use of ANNs for regression problems concerned predictions for 305-day lactation yield in Polish Holstein-Friesian cows based on monthly test-day results [48]. The following 7 input variables were used: mean 305-day milk yield of the barns in which the cows were utilized, days in milk, mean test-day milk yield in the first, second, third and fourth month of the research period and calving month.…”
Section: Regression Tasks -Milk Yield Prediction In Cattlementioning
confidence: 99%